Morphology of Electrochemically and Chemically Deposited Metals - Popov, Konstantin I.; Djokic´, Stojan S.; Nikolic´, Nebojsˇa D.; Jovic´, Vladimir D. (Springer International Publishing : Imprint: Springer, 2016)
This book describes the newest achievements in the area of electrochemically and chemically deposited metals and alloys. In particular, the book is devoted to the surface morphology of deposited metals and alloys. It contains an in-depth analysis of the influence of the parameters of electrodeposition or chemical deposition of metals and alloys, which will likely lead to technological advances in industrial settings world-wide. Professionals in electrometallurgical and electroplating plants will find the book indispensable. This book will also be useful in the automotive, aerospace, electronics, energy device and biomedical industries. In academia, researchers in electrodeposition at both undergraduate and graduate levels will find this book a very valuable resource for their courses and projects. .